Uso de probióticos na depressão - FRANCO, Lia Valéria Dantas (2023)
Use of probiotics in depression — Depression is considered a dominant factor for causes of disability and has a major impact on the global burden of disease — Diagnosis is often made late when symptoms get worse, as they can be confused with organic diseases (RAKEL, 1999). In addition to genetic or environmental factors, one of the hypotheses for the occurrence of depression is related to the microbiota and some adjuvants such as probiotics can improve symptoms of depression, through the modulation of this intestinal microbiota for energy and stimulation of the immune system. The main objective is to verify the effectiveness of the use of probiotics for use as an adjunct in the treatment of depression, to improve symptoms. The work is a systematic review in databases such as PubMed, Scielo and Google Scholar. The articles researched for the development of the review comprise between the years 2011 to 2021. The descriptors used were: microbiota, depression and probiotics. Englishlanguage articles were included in the search.